2010
DOI: 10.1515/cclm.2010.274
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of serum macrophage-colony stimulating factor (M-CSF) in esophageal cancer patients and its comparison with classical tumor markers

Abstract: Our findings suggest the potential usefulness of serum M-CSF concentrations as a tumor marker for EC, especially in combination with SCC-Ag. However, the diagnostic value of this cytokine may be limited because of its non-specific nature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
16
5
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 20 publications
6
16
5
1
Order By: Relevance
“…It suggests that use of MMP-2 and TIMP-2 in combination with different imaging techniques could be a predicting tool giving important preoperative information in staging of EC patients. The serum levels of CEA increased significantly with tumor stage, tumor size and presence of nodal metastases, what is in line with our previous study [33].…”
Section: Discussionsupporting
confidence: 92%
“…It suggests that use of MMP-2 and TIMP-2 in combination with different imaging techniques could be a predicting tool giving important preoperative information in staging of EC patients. The serum levels of CEA increased significantly with tumor stage, tumor size and presence of nodal metastases, what is in line with our previous study [33].…”
Section: Discussionsupporting
confidence: 92%
“…The frequency of increased concentrations of IL-6 established in the current paper was higher than those obtained in our previous studies, where we assessed the diagnostic sensitivity of other biomarkers, including matrix metalloproteinase 9 (MMP-9) in EC and ESCC patients (70% and 75%, respectively) 18,21 as well as hematopoietic growth factors, such as macrophage colony stimulating factor (M-CSF; 71% in EC patients and 70% in ESCC subgroup). 22 In our present paper, diagnostic specificity of IL-6 levels was slightly lower when compared with classic tumor markers in EC, ESCC, and AD subgroups. We found that the IL-6 AUC were notably larger than the AUC for CEA and SCC-Ag, and the highest AUC was found for IL-6 in ESCC subgroup (0.9241).…”
Section: Discussioncontrasting
confidence: 44%
“…The combined used of IL‐6 with CEA or SCC‐Ag slightly improved the diagnostic sensitivity and were higher than those of classic tumor markers (CEA with SCC‐Ag). The frequency of increased concentrations of IL‐6 established in the current paper was higher than those obtained in our previous studies, where we assessed the diagnostic sensitivity of other biomarkers, including matrix metalloproteinase 9 (MMP‐9) in EC and ESCC patients (70% and 75%, respectively) 18,21 as well as hematopoietic growth factors, such as macrophage colony stimulating factor (M‐CSF; 71% in EC patients and 70% in ESCC subgroup) 22 . In our present paper, diagnostic specificity of IL‐6 levels was slightly lower when compared with classic tumor markers in EC, ESCC, and AD subgroups.…”
Section: Discussionmentioning
confidence: 56%
“…Several studies have demonstrated the increase of anti-inflammatory cytokines and the higher frequency of suppressive cells in the bloodstream and lymph nodes from cancer patients. The detection of higher amounts of cytokines like TGF-beta [32], M-CSF [33], and IL-6 [34, 35] in patients' serum could suggest that the tumor presence affects cells in distant organs, thus resulting in systemic alterations which could allow tumors not only to grow locally unchecked but also to metastasize without an effective immune barrier. In agreement with that are: the higher frequency of myeloid-derived suppressor cells (MDSCs) (a group of immature but potent suppressor cells capable of down-regulating anti-tumor immunity) found in cancer patients' circulation [36]; the decreased frequency of circulating and tumor-infiltrating myeloid DCs [37, 38]; and the CD4 lymphopenia observed in cancer patients [3941]; all three important alterations of immune homeostasis in cancer patients that, consequently, hamper the effectiveness of their treatment.…”
Section: The Tumor Microenvironment: a Tolerogenic Milieumentioning
confidence: 99%